Case report: Rare variants in the MTRR gene, 66GG and 524TT cause hyperhomocysteinemia and folic acid deficiency linked to schizophrenia - Huang, Chih-Chia (Frontiers in Psychiatry, 2024)
We present an adult patient with schizophrenia who was later found to have hyperhomocysteinemia, a condition that increases the risk of several diseases, due to a deficiency in folic acid. Although folic acid supplementation quickly normalized the hyperhomocysteinemia and folic acid levels, it did not significantly improve the overall mental and cognitive health. Genotype analysis was performed and the patient was found to have two pathogenic variants in the MTRR gene, 66GG and 524TT, which encodes for methionine synthase reductase (MSR), an enzyme crucial for homocysteine metabolism. The results can shed light on the reasons behind the patient's hyperhomocysteinemia and folic acid deficiency. Hyperhomocysteinemia confers an increased risk of several diseases. Indeed, the patient has neurodevelopment and cardiovascular health problems for decades. Given the rarity of the condition and the nonspecific nature of the symptoms, the detection of hyperhomocysteinemia or MSR deficiency can often be delayed or overlooked. Considering the potential irreversible and detrimental consequences of prolonged hyperhomocysteinemia and folic acid deficiency that our patient is likely experiencing, we suggest that clinicians be vigilant for associated signs when they encounter adolescents exhibiting psychotic symptoms, especially those with additional physical symptoms and a history of resistance to treatment.